Shock-cloud interaction in RX J1713.7-3946 : evidence for cosmic-ray acceleration in the Young Vhe [gamma]-ray supernova remnant /: evidence for cosmic-ray acceleration in the Young Vhe [gamma]-ray supernova remnant. (2017) - Sano, Hidetoshi
No abstract available